Memotret Interaksi Nilai-nilai Budaya dalam Aktivitas Dakwah - Abdul Wahid (LP2M IAI Muhammadiyah Sinjai, 2021)
This paper is about photographing the interaction of cultural values ​​in the da'wah process. Culture and humans cannot be separated because humans naturally have the potential to give birth to culture. In that context, it is impossible for the da'wah process to be separated from the culture that develops in the community. The interaction of culture and da'wah is in positioning humans as the subject and object of da'wah. Religion exists not to eliminate the culture that has been produced by humans, but on the contrary to provide reinforcement with religious values, so that cultural interactions are born and then form an Islamic cultural model, namely; a cultural model that is in line with the values ​​and principles of religious teachings, this is in line with the message of Allah SWT. contained in QS. al-'Araf[7]:199